2018
DOI: 10.1155/2018/4593875
|View full text |Cite
|
Sign up to set email alerts
|

Modern Myoma Treatment in the Last 20 Years: A Review of the Literature

Abstract: Myomas, also known as fibroids, are a specific characteristic of the human species. No other primates develop fibroids. At a cellular level, myomas are benign hyperplastic lesions of uterine smooth muscle cells. There are interesting theoretical concepts that link the development of myomas in humans with the highly specific process of childbirth from an upright position and the resulting need for greatly increased “expulsive” forces during labor. Myomas might be the price our species pays for our bipedal and h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
11

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 33 publications
0
15
0
11
Order By: Relevance
“…Lorsque les patientes sont symptomatiques, le nombre, la taille et / ou la localisation des fibromes sont des déterminants critiques de leurs manifestations cliniques. Les symptômes les plus fréquemment rapportés comprennent des saignements menstruels abondants, une dysménorrhée, des douleurs non cycliques, des symptômes urinaires, de la fatigue et de la constipation [ 3 , 11 , 20 ]. Une méta-analyse récente a démontré que les fibromes sous-muqueux, intra-muros et sous-séreux ont des effets différents sur la fertilité et qu'ils sont principalement liés à des lésions sous-muqueuses entraînant des défauts d'implantation [ 12 ].…”
Section: Discussionunclassified
“…Lorsque les patientes sont symptomatiques, le nombre, la taille et / ou la localisation des fibromes sont des déterminants critiques de leurs manifestations cliniques. Les symptômes les plus fréquemment rapportés comprennent des saignements menstruels abondants, une dysménorrhée, des douleurs non cycliques, des symptômes urinaires, de la fatigue et de la constipation [ 3 , 11 , 20 ]. Une méta-analyse récente a démontré que les fibromes sous-muqueux, intra-muros et sous-séreux ont des effets différents sur la fertilité et qu'ils sont principalement liés à des lésions sous-muqueuses entraînant des défauts d'implantation [ 12 ].…”
Section: Discussionunclassified
“…The incidence of uterine fibroids in the childbearing age and perimenopausal period are higher, and the growth rate of fibroids is very fast [26]. However, the lesions of some patients after menopause will gradually shrink and even disappear [27]. Previous studies [28][29][30] have reported that the occurrence and development of multiple uterine fibroids is associated with changes of female hormones, the concentration of estradiol in myoma tissue is significantly higher than that of normal myometrial tissue, and the concentration of estrogen receptor is also significantly higher than the surrounding area of normal myometrial tissue, while the concentration of estradiol to estrone conversion is lower, it can be seen that progesterone, progesterone and its receptors can promote the occurrence and development of uterine fibroids.…”
Section: Discussionmentioning
confidence: 99%
“…Gejala mioma uteri diantaranya adalah menorrhagia, aktivitas fisik yang terganggu (Stewart et al, 2013), adanya massa panggul dan nyeri panggul (Donnez andDolmans, 2016), anemia, inkontinensia urin (McWilliams andChennathukuzhi, 2017), perdarahan vagina yang berkepanjangan dan dapat menyebabkan infertilitas (Aleksandrovych et al, 2015). Dalam kasus yang ekstrim, dapat terjadi obstruksi ureter dan menyebabkan kematian (El Balat et al, 2018). Selain itu hampir sepertiga penderita mioma uteri kehilangan pekerjaan, hampir seperempat penderita merasa bahwa gejala miomia uteri menghalangi potensi kariernya (Borah et al, 2013).…”
Section: Abstract: Reproductive Health Uterine Myoma Risk Factorsunclassified
“…Mioma uteri adalah sumber morbiditas utama bagi wanita usia subur (Stewart et al, 2013) dan merupakan indikasi utama untuk histerektomi (Wise et al, 2015). Saat ini ada beberapa pilihan untuk mengobati mioma uteri, mulai dari pendekatan yang paling konservatif hingga pendekatan yang paling invasif tergantung kondisi penderita (El Balat et al, 2018). Terdapat sekitar 25%-50% penderita mioma uteri harus melakukan pembedahan (miomektomi/ histerektomi) untuk mengatasi mioma-nya secara definitif.…”
Section: Pembahasanunclassified